The control over public budget as one dimension of "war culture": the case of Prodav notice - Rodrigues Moreira, Henrique (Revista de Ciências Sociais, 2022)
The case of the BRDE/FSA PRODAV 2018 Notice, created to promote audiovisual productions and which one was temporarily suspended according to president Jair Bolsonaro’s interests, is very illustrative to understand the cultural and economic dimensions of what has been called “bolsonarism”. The attempt by Jair Bolsonaro's administration to abort the event's progress points in two directions: cultural disrespect and relational hostility towards the LGBTQI+ community, seen by some interpretations as a part of a “war culture” undertaken by bolsonarism; and how the meanings of these relationships affect the processes of transferring resources, goods or services. We take use of economic sociology to draw the discussion.